2008
DOI: 10.1038/oby.2007.45
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate Hydrochloride Increases Energy Expenditure in Healthy Adults

Abstract: Objective: To examine the effects of methylphenidate hydrochloride (MPH) on resting energy expenditure (REE) and postprandial energy expenditure (PEE) and substrate partitioning. Methods and Procedures: Seven healthy men and seven healthy women participated in this double-blind, randomized, placebo-controlled, crossover study. MPH (0.5 mg/kg) or placebo was administered orally in the fasting state, 60 min before a REE measurement, and 90 min before a standardized breakfast of ~650 kcal. REE, PEE, and respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…One of these three was also taking methylphenidate for attention-deficit disorder. Methylphenidate is reported to increase REE and suppress food intake [19, 20]. In spite of this, our patients still had a lower than expected REE indicating that these medicines were unlikely to be confounders in our analysis.…”
Section: Discussionmentioning
confidence: 56%
“…One of these three was also taking methylphenidate for attention-deficit disorder. Methylphenidate is reported to increase REE and suppress food intake [19, 20]. In spite of this, our patients still had a lower than expected REE indicating that these medicines were unlikely to be confounders in our analysis.…”
Section: Discussionmentioning
confidence: 56%
“…The Weir (1949) and Zuntz (1901) equations have been used previously in research in different fields, including Public Health (Doucet et al 2003;Lorello et al 2008;Shew et al 2000) and Sport Sciences (Brugniaux et al 2010;McDaniel et al 2002;Stewart and Stewart 2007;Westerterp et al 1992). Within the Sport Sciences, these EE equations have been used in the study of disciplines such as ultra-endurance running (Stewart and Stewart 2007), cycling (McDaniel et al 2002) and mountaineering (Westerterp et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The noradrenergic sympathomimetic agent phentermine is approved as a short‐duration (<3 months) adjunct to lifestyle modification, although it should be noted that combination phentermine/topiramate ER is indicated for long‐term treatment in the United States. The exact mechanism of action of phentermine is unknown, but it appears to act within the hypothalamus to upregulate noradrenaline, resulting in the stimulation of β 2 ‐adrenergic receptors to induce appetite suppression; it also appears to inhibit monoamine oxidase, potentiating the effect of serotonin and possibly increasing basal metabolic rate . Phentermine is associated with a 3.6 kg (95% confidence interval (CI), 0.6–6.0 kg) greater weight loss compared with placebo in studies …”
Section: Pharmacotherapymentioning
confidence: 99%
“…Adverse effects related to phentermine are attributable to its stimulant properties and include dry mouth, agitation, insomnia and decreased concentration . Significant cardiovascular and neurocognitive complications were also historically attributed to this therapy; however, a recent meta‐analysis of phentermine monotherapy studies concluded that phentermine is not associated with any serious adverse events .…”
Section: Pharmacotherapymentioning
confidence: 99%